The ethical case for placebo control in HIV-cure-related studies with ART interruption - Monica Magalhaes; Daniel R. Kuritzkes; Nir Eyal (Elsevier, 2022)
Many studies that seek to cure HIV must ask participants to interrupt their antiretroviral treatment. In such circumstances, is it permissible to include a placebo group in the study? We explain why doing so is a scientific and an ethical necessity, and more benign than imagined.